The discursive roots of the community: a genealogy of the curriculum (Bilingual edition: English/Portuguese) - Barry M. Franklin (Universidade Federal de Uberlândia, 2016)
Abstract: This article explores discourses constructed about the curriculum in the United States. The highlighted period goes from the 1890s to the first thirty years of the 20th century. Attention is given to the documents produced by the National Education Association (NEA) and the discursive formations outlined by three key individuals: Edward L. Thorndike, Ross L. Finney, and John Dewey. The main issue is about the curriculum as an effort to institute and perpetuate group living and the dispute around the idea of community. Keywords: Curriculum, Community, Dewey, Thorndike, Finney. Â Resumo: Este artigo explora discursos construídos em torno do currículo nos Estados Unidos. O período destacado se situa entre os anos de 1890 e os primeiros trinta anos do século XX. Destacam-se os documentos produzidos pela National Education Association (NEA) e as formações discursivas delineadas por três indivíduos chave: Edward L. Thorndike, Ross L. Finney e John Dewey. A questão central abordada diz respeito ao currículo como esforço de instituir e perpetuar a vida grupal e a disputa pela ideia de comunidade Palavras-chave: Currículo, Comunidade, Dewey, Thorndike, Finney. Resumen Este artículo explora los discursos construidos en torno del currículo en los Estados Unidos. El período destacado se situa entre los aÃ±os de 1890 y los primeros treinta aÃ±os del siglo XX. Se destacan los documentos produzidos por la Asociación Nacional de Educación (NEA) y las formaciones discursivas delineadas por tres individuos clave: Edward L. Thorndike, Ross L. Finney y John Dewey. La cuestión abordada considera el currículo como el esfuerzo de instituir y perpetuar la vida grupal y la disputa por la idea de comunidad. Palabras-clave: Currículo, Comunidad, Dewey, Thorndike, Finney.